(untitled) (Research, Society and Development, 2021)
Hypertension represents one of the main risk factors associated with the development of cardiovascular diseases. Adherence of the patient to the therapeutic regimen is a primary factor for the efficacy of the treatment. The health professional performance contributing to the choice of the most convenient, safe and correct treatment. This study aimed to assess the influence of pharmaceutical intervention in the adherence of hypertensive patients’ therapy. The study was carried out in the Estrela do Norte settlement, community of Sanharó, rural area of the municipality of Montes Claros, North of Minas Gerais. The sample consisted of 21 individuals aged between 40 and 86 years of both genres. The research had a direct approach with descriptive method of quantitative character. A form was applied, through individual home visits and educational actions developed. After 6 months the questionnaire was reapplied. The interviewees were mostly female e elderly. After the follow-up, there were changes of opinions and attitudes of the participants, which raised adherence to pharmacotherapy, understanding about the disease and the importance of the correct therapeutic segment. It is concluded that the Pharmacotherapeutic intervention positivily influences adherence to therapy and the pharmacist is an important professional to compose the Family Health Strategy team. The pharmacist must be able to seek educational measures that facilitate the understanding of patients about their health status, ways to prevent and control the disease, besides to encouraging and showing the importance of self-care.